Experimental and numerical investigation of specific energy consumption of the two-stage pneumatic-fluidized bed drying of suspension-grade polyvinyl chloride. Issue 2 (11th January 2022) - Dorfeshan, Masoud; Mehrzad, Salem; Hajidavalloo, Ebrahim
Abstract: The multistage drying system is one of the novel methods that has small specific energy consumption (SEC) compared to the conventional single drying systems. Rotary and fluidized bed dryers are the conventional drying systems of suspension-grade polyvinyl chloride (S-PVC). This article describes the energy consumption characteristics of a two-stage pneumatic fluidized bed drying system for drying of S-PVC. Computational Fluid Dynamics is used to anticipate the hydrodynamics and drying mechanisms with Eulerian–Lagrangian and Eulerian–Eulerian approach in the pneumatic dryer and fluidized bed dryer, respectively. The experimental study is accomplished using spiral pneumatic and a fluidized bed dryer. The investigation of the SEC and influence of a two-stage drying system on S-PVC drying has been set as the main target. The result shows that by using the two-stage pneumatic-fluidized bed drying in certain conditions, the SEC is reduced up to 8255 kJ/kg and an average of 5260 kJ/kg compared with fluidized bed single-stage drying.